ACCOUNTING STUDENTS’ WHISTLEBLOWING INTENTIONS: WHAT ARE THE DRIVERS? - Almas Hilman; Agus Purwanto (Diponegoro Journal of Accounting, 2023)
This research examines the determinants of accounting students’ whistleblowing intentions. A questionnaire is shared with 258 final-year accounting students, with 164 concluding as a final sample. The model is tested using the partial least square of structural equation modelling analysis. The results demonstrated the positive effect of the learning environment, anticipatory socialization, professional commitment, and perceived moral intensity on accounting students' whistleblowing intentions. As the external driver significantly affects students' whistleblowing intentions, this study suggests improvement in several areas, such as physical and non-physical facilities and the lectures' traits concerning ethical-related things. Additionally, as leading actors, students must be aware of the necessity of ethical issues to boost better ethical decisions.The findings provide additional substance to expand the research concerning knowledge in this field.